2021
DOI: 10.1088/1361-6641/ac038d
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into water-induced surface oxidization of GaN lamella structure

Abstract: The interaction between gallium nitride (GaN) and H 2 O has been thoroughly investigated using a novel methodology involving the fabrication of a well-defined nanometer scale GaN lamella by means of a focused ion beam milling technique. Electrical characterization results show that the exposure of the GaN surface to water at room temperature causes the device resistivity to continuously increase, which makes the GaN lamella a stable polar liquid sensor. To explain the relationship between the reduced conductiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
(86 reference statements)
0
3
0
Order By: Relevance
“…This is consistent that the degradation of the AlGaN barrier is reducing the 2DEG density in the channel, which will directly reduce the contact resistance at the interface. 35,36 The structural integrity of the contact regions is further confirmed in transmission electron microscopy (TEM) 37,38 images of the TLM samples before and after the full 72 h testing period as shown in Fig. 4, which are hereinafter referred to as the pristine and HTexposed samples, respectively.…”
mentioning
confidence: 82%
“…This is consistent that the degradation of the AlGaN barrier is reducing the 2DEG density in the channel, which will directly reduce the contact resistance at the interface. 35,36 The structural integrity of the contact regions is further confirmed in transmission electron microscopy (TEM) 37,38 images of the TLM samples before and after the full 72 h testing period as shown in Fig. 4, which are hereinafter referred to as the pristine and HTexposed samples, respectively.…”
mentioning
confidence: 82%
“…The XPS analysis we conducted exhibits that, for the oxidized-GaN, the O 1s signal was deconvoluted into three components at positions of 530.8, 532, and 532.8 eV assignable to Ga–O–Ga, Ga–OH, and molecularly adsorbed H 2 O, respectively. Based on our findings, it was concluded that, upon exposing the device to water and applying an electrical potential, the water molecules adsorbed on the polar GaN surface spontaneously undergo dissociation.…”
Section: Fundamental Understanding Of the Processes Involved In Gan-b...mentioning
confidence: 99%
“…Therefore, further research is required to develop a model that brings the GaN surface one step closer to practical cases. 85 In our computational study, 100 we employed the GGA + 1/2 functional to calculate the electronic properties of GaN and oxidized-GaN in their bulk forms. The oxidized GaN, under a 3.1% substitution rate, exhibited a smaller bandgap value of 3.086 eV compared to GaN (3.348 eV).…”
Section: Computational Study: Dft and MD Study Of The Interaction Pro...mentioning
confidence: 99%